2022
DOI: 10.3390/ijms231911198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Glycinin on Oxidative Damage, Apoptosis and Tight Junction in the Intestine of Juvenile Hybrid Yellow Catfish, Pelteobagrus fulvidraco ♀ × Pelteobaggrus vachelli ♂

Abstract: The objective of this study was to examine the influences of glycinin for growth and intestinal structural integrity related to oxidative damage, apoptosis and tight junction of juvenile hybrid yellow catfish (Pelteobagrus fulvidraco ♀ × Pelteobaggrus vachelli ♂). Fish (initial weight, 1.02 ± 0.01 g) were fed diets containing five different levels of glycinin at 0%, 2%, 4%, 6%, and 8% for 8 weeks. The results demonstrated that dietary glycinin levels had a negative correlation with final weight, feed intake, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 65 publications
2
9
0
Order By: Relevance
“…Unexpectedly, 10% glycinin addition achieved better growth rate and feed utilization than did the SBM diet and had a growth rate and feed utilization similar to that of the control, although its growth rate and feed utilization were inferior to that of 4.5% glycinin addition. Similarly, the reduced growth rate and feed utilization were observed in grass carp ( Ctenopharyngodon idella ) [ 51 ], hybrid yellow catfish ( Pelteobagrus fulvidraco ♀ × Pelteobaggrus vachelli ♂) [ 34 ] and hybrid grouper [ 25 ] when they were fed the diets containing 6–8% glycinin, and the opposite results occurred for those fed the diets containing 2–4% glycinin, as compared with FM diets. These findings indicate that dietary high-glycinin content addition does not constrain growth, and the intermediate-glycinin content addition exhibits superior growth performance to that of the control diet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unexpectedly, 10% glycinin addition achieved better growth rate and feed utilization than did the SBM diet and had a growth rate and feed utilization similar to that of the control, although its growth rate and feed utilization were inferior to that of 4.5% glycinin addition. Similarly, the reduced growth rate and feed utilization were observed in grass carp ( Ctenopharyngodon idella ) [ 51 ], hybrid yellow catfish ( Pelteobagrus fulvidraco ♀ × Pelteobaggrus vachelli ♂) [ 34 ] and hybrid grouper [ 25 ] when they were fed the diets containing 6–8% glycinin, and the opposite results occurred for those fed the diets containing 2–4% glycinin, as compared with FM diets. These findings indicate that dietary high-glycinin content addition does not constrain growth, and the intermediate-glycinin content addition exhibits superior growth performance to that of the control diet.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the majority of the research focuses on the sensitization of the two types of SAPs in animals and their underlying mechanisms. Recent results showed that SAPs exhibit high antigenic activity [ 22 , 23 , 24 , 25 , 26 ], induce specific antigen–antibody reactions and delay hypersensitivity mediated by T lymphoid cells—by stimulating the immune system [ 15 , 22 , 27 , 28 ]; trigger reactive oxygen, leading to oxidative stress in intestinal epithelial cells [ 5 , 27 , 29 , 30 ] and intestinal epithelial cell apoptosis and damage [ 15 , 28 , 31 , 32 ]; and develop into symptoms such as enteritis and allergic reactions [ 22 , 24 , 26 , 33 ], eventually leading to poor growth [ 34 ]. In terms of oxidative stress, many factors in diets, such as polypropylene microplastics [ 35 ] and nitrite [ 36 ], can cause oxidative stress in fish and injure tissues and organs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, down-regulated mRNA levels of bcl-2 and bcl-xL genes and up-regulated mRNA levels of NF-kB and TNF-a genes were observed in fish fed the SBM and 7% b-conglycinin diets, which agreed with the results in a study with grass carp fed high bconglycinin diets (Duan et al, 2019a). Although there are few research reports on the effect of dietary b-conglycinin levels on the intestinal cell apoptosis of fish, glycinin, another major antigen protein, has also been found to render this effect in other fish, that is, high glycinin diets down-regulated intestinal bcl-2 mRNA expression and up-regulated intestinal TNF-a mRNA expression (Zhang Y. L. et al, 2021;Yi et al, 2022). Therefore, dietary high bconglycinin could enhance intestinal cell apoptosis by downregulating anti-apoptosis bcl-2 and up-regulating expression of proapoptosis TNF-a through NF-kB signaling pathway.…”
Section: Intestinal Cell Apoptosismentioning
confidence: 99%
“…The two types of antigen protein, therefore, have become the major concern for studying sensitization on animals and its underlying mechanisms (He et al, 2015). Recent results showed that soy antigen proteins have high antigenic activity (Li et al, 2017;Hu et al, 2021;Shan et al, 2021), promote intestinal permeability (Han et al, 2019;Scott et al, 2019;Zhang Y. L. et al, 2021), induce specific antigenantibody reactions and T lymphoid cell-mediated hypersensitivity delay by stimulating the immune system (Gu et al, 2016a;Li et al, 2020;He et al, 2022), trigger apoptosis of intestinal epitheliums (Peng et al, 2018;Duan et al, 2019a;Peng et al, 2019;Wang et al, 2022;Yi et al, 2022) through the production of reactive oxygen species (Li et al, 2019;Li et al, 2020;Zhang et al, 2020;Yi et al, 2022), disrupt intestinal microbiota homeostasis (Han et al, 2019;He et al, 2022) and develop into pathological reactions with allergies and enteritis as the main symptoms (Zhang et al, 2013;Booman et al, 2018;Zheng et al, 2020;Zhu et al, 2021), eventually leading to poor growth (Zhao et al, 2021;Yi et al, 2022). Great progress has been made in this regard in recent years, but the research on the negative impact of soy antigen proteins on fish is limited, and the underlying mechanisms involving enteritis and allergy induced by soy antigen proteins in fish are still unclear.…”
Section: Introductionmentioning
confidence: 99%